Pengaruh Audit Operasional Dan Pengendalian Internal Terhadap Kinerja Perusahaan (Studi Kasus Pada CV. KYNI Sukses) - Endang Setyorini; Har Agus Turjayawan; Yenni Elfiza Abbas (Cakrawala Akuntansi & Manajemen, 2022)
Dry clean laundry services are small and medium enterprizes (UKM) which are engaged in washing clothes, bed sheets, bed cover and others. Every laundry servies are required to be a service organization that focuses in customer service, so it has an ability to sustain the company operational audit and internal control are also implemented by CV Kyny Sukses for improving the company performance. This research is a causal comparative study with quantitative approach. This research proves that there is a positive and significant influence between operational audit on company performance. Meanwhile, internal control has a negative effect on CV Kyni Sukses’s company performance and does not has a significant effect. From the test result of the coefficient of determination (R2) which produces independent variables, namely operational audits and internal control on CV Kyni Sukses performance is equal to 19,8%. While the remaining 80,2% can be influenced by other variable such as the company’s financial condition, SOP system that applied in this company. This study proves that there is a positive and significant influence between operational audits on company performance